The Process of Sustainable Development and the Linkage to the Social - Ecological Transformation in the World and in Vietnam - Thanh Son, Vo (VNU Journal of Science: Policy and Management Studies, 2021)
Sustainable development is a global trend to build a prosperous society, especially to promote green growth towards ecological approach and based on sustainable use of natural resources in the context of climate change. This article, therefore, is an attempt to synthesize the sustainable development process in the world, from the initial awareness of the role of the environment in the development process in the 1980s, to the development of Agenda 21 in the 1990s, to develop and implement the 2030 agenda for sustainable development in the present time. The change in awareness and practice of sustainable development also demonstrates the trend of social-ecological transformation as a development trend and is an urgent requirement towards building a prosperous and sustainable society. Integrating sustainable development into international and national development policies can be considered as a form of promoting social-ecological transformation. The UNESCO’ system of Biosphere Reserves as a model for promoting sustainable development initiatives towards harmony between people and nature can be considered as a model of a social-ecological system. Vietnam as a country actively participating the sustainable development process in the world has made great efforts to build a prosperous and sustainable society. Keywords: Sustainable development, social - ecological transformation, Vietnam. References [1] United Nations, Agenda 2, United Nations Conference on Environment & Development Rio de Janerio, Brazil, 3 to 14 June 1992, pp. 351. [2] IUCN, UNEP, WWF, World Conservation Strategy: Living Resource Conservation for Sustainable Development, 1980, pp. 77. [3] United Nations, Our Common Future, Oxford: Oxford University Press, 1987. [4] Meadows, H. Donella, Meadows, L. Dennis, Randers, Jørgen; Behrens III, W. William, The Limits to Growth; A Report for the Club of Rome's Project on the Predicament of Mankind. New York: Universe Books, 1972. [5] IUCN, UNEP và WWF, Caring for the Earth: A Strategy for Sustainable Living (in Vietnamse), Translation from original copy, Hanoi: Science and Technology Publishing House, 1993, pp. 240. [6] Millennium Ecosystem Assessment (MEA), Ecosystems and Human Well-being: Synthesis. Island Press, Washington, DC, 2005, pp. 102. [7] United Nations, Global Sustainable Development Report, 2015a, pp. 198. [8] United Nations, Transforming our world: the 2030 Agenda for Sustainable Development. A/RES/70/1, 2015b, pp. 40. [9] Liliane Danso-Dahmen, Philip Degenhardt (Eds.), Social-Ecological Transformation Perspectives from Asia and Europe. Published by the Rosa-Luxemburg-Stiftung, 2019, pp. 111. [10] Bass Steve, Conceptual Frameworks for Integrating Sustainable Development Dimensions Paper for UNDESA/UNEP/UNDP Workshop on SD Integration tools, Geneva, 14-15 October 2015. [11] Cejudo, Guillermo M and Cynthia Michel, Addressing fragmented government action: Coordination, coherence, and integration. Paper to be presented at the 2nd International Conference in Public Policy, Milan, July 2015, pp. 22. [12] UN-DESA, Integrated Approaches to Sustainable Development Planning and Implementation. Report of the Capacity Building Workshop and Expert Group Meeting, Department of Economic & Social Affairs, 2015. [13] ESDN, Horizontal Policy Integration and Sustainable Development: Conceptual remarks and governance examples. ESDN Quarterly Report June 2009, http://www.sd-network.eu/quarterly%20reports/report%20files/pdf/2009-June-Horizontal_Policy_Integration_and_Sustainable_Development.pdf. [14] OECD, Guidance on Sustainability Impact Assessment. Organisation for Economic Co-operation and Development, 2010. [15] DFID, Sustainable Livelihoods Guidance Sheets. April 1999, https://www.ennonline.net/dfidsustainableliving. [16] Adams, W.M, The Future of Sustainability: Re-thinking Environment and Development in the Twenty-first Century. Report of the IUCN Renowned Thinkers Meeting, 29-31 January 2006, pp. 18. https://portals.iucn.org/library/sites/library/files/documents/Rep-2006-002.pdf. [17] J. Rockström et al., A safe operating space for humanity, Nature 461(7263), 2009a, 472–475. [18] J. Rockström et al., Planetary Boundaries: Exploring the Safe Operating Space for Humanity. Ecology and Society 14(2), 2009b, 32. [19] Steffen, Will, K. Richardson, J. Rockström, S.E. Cornell, I. Fetzer, E.M. Bennett, R. Biggs, S.R. Carpenter, Wim de Vries, Cynthia A. de Wit, Carl Folke, Dieter Gerten, J. Heinke, G.M. Mace, Linn M. Persson, Veerabhadran Ramanathan, B. Reyers, Sverker Sörlin, Planetary boundaries: Guiding human development on a changing planet. Science 347, 1259855 (2015). DOI: 10.1126/science.1259855. [20] Pisano, Umberto and Gerald Berger, Planetary Boundaries for Sustainable Development: From a conceptual perspective to national applications. ESDN Quarterly Report 30 – October 2013, ESDN Quarterly Report N.30. European Sustainable Development Network, 31 pages, http://www.sd-network.eu/quarterly%20reports/report%20files/pdf/2013-October-Planetary_Boundaries_for_SD.pdf [21] Raworth Kate, From Will these Sustainable Development Goals get us into the doughnut (aka a safe and just space for humanity)? Duncan Green’s discussion on Raworth’s doughnut and SDGs. 2014, http://oxfamblogs.org/fp2p/will-these-sustainable-development-goals-get-us-into-the-doughnut-aka-a-safe-and-just-space-for-humanity-guest-post-from-kate-raworth/ [22] Vietnam, Implementation of Sustainable Development: National Report at the UN Conference on Sustainable Development (Rio+20) (in Vietnamese), Ministry of Planning and Investment, Hanoi, May 2012, pp. 82. [23] Vietnam, Voluntary National Review on the Implementation of the Sustainable Development Goals ,Ministry of Planning and Investment, 2018, pp. 90 (in Vietnamese). [24] IMHEN, Integrating Climate Change into Socio-economic Development Plans Viet Nam Institute of Meteorology, Hydrology and Climate Change, Viet Nam Publishing House of Natural Resources, Environment and Cartography, Hanoi, 2012, pp.137 (in Vietnamese). [25] T. Thuc, H.T.L. Huong and D. M. Trang, Technical guidance on integrating climate change into development planning Viet Nam Institute of Meteorology, Hydrology and Climate Change, Viet Nam Publishing House of Natural Resources, Environment and Cartography, Hanoi, 2012, pp. 69 (in Vietnamese). [26] MPI and UNDP, A study on advanced strategic environmental assessment tools for the sustainability assessment of development planning projects, A project on "Strengthening capacity to integrate sustainable development and climate change in planning in Vietnam, Hanoi, 2011, pp. 79 (in Vietnamese). [27] Minister of the Ministry of Planning and Investment, Circular No. 02/2013/TT-BKHDT dated March 27, 2013 guiding the implementation of a number of contents of the Strategy for Sustainable Development in Vietnam for the period 2011-2020), 2013 (in Vietnamese). [28] V.T. Son and T.T. Phuong, Monitoring and evaluation criteria for management effectiveness for biosphere reserves: Practices in the world and applicability in Vietnam (in Vietnamese). Journal of Environment, Topic II, 2018, 12-15. [29] German MAB National Committee. Criteria for Designation and Evaluation of UNESCO Biosphere Reserves in Germany. Publisher: German National Committee for the UNESCO Programme “Man and the Biosphere” (MAB), 1996, pp. 65. [30] V.T. Son et al, Final report of the independent State-level scientific and technological project titled “Research on developing a set of criteria and procedures for monitoring and evaluating the efficiency of management of biosphere reserves in Vietnam”, Code DTLXH, 20/15.2018.